Sonodynamic effect of hematoporphyrin monomethyl ether on ligature-induced periodontitis in rats - Zhuang DS; Han JL; Bi LJ; Wang YP; Hao YR; Zhou Q; Cao WW (Dove Medical Press, 2015)
Deshu Zhuang,1 Jialong Han,1 Liangjia Bi,1 Yueping Wang,1 Yanru Hao,2 Qi Zhou,3 Wenwu Cao3,4 1Department of Stomatology, The Fourth Affiliated Hospital, Harbin Medical University, Harbin, People’s Republic of China; 2Department of Stomatology, The First Affiliated Hospital, Harbin Medical University, Harbin, People’s Republic of China; 3Condensed Matter Science and Technology Institute, Harbin Institute of Technology, Harbin, People’s Republic of China; 4Department of Mathematics and Materials Research Institute, The Pennsylvania State University, University Park, PA, USA Objectives: The aim of this study was to perform a histological evaluation of sonodynamic therapy (SDT) of hematoporphyrin monomethyl ether (HMME) on artificially induced periodontal disease in rats.Methods: Submerging ligatures were placed at the subgingival region of the first maxillary molar in rats. Eighty rats were randomly assigned into four groups: group 1 received no treatment; group 2 was subjected to 50 µg/mL HMME alone; group 3 was treated with low-intensity ultrasound alone (1 W/cm2); and group 4 was treated with 50 µg/mL HMME plus ultrasound irradiation (1 MHz, 30 minutes). Ten rats in each group were euthanized at 7 and 15 days, and periodontal tissue samples were taken for histological examination.Results: The animals treated by SDT showed less bone loss (P<0.05) at all experimental periods than the other three groups. No significant differences were found between the control and HMME groups (P>0.05).Conclusion: Our results suggest that HMME-mediated SDT can effectively alleviate the periodontal tissue destruction in artificially induced periodontitis in rats. Hence, SDT may have good clinic potential as a noninvasive treatment of periodontal diseases. Keywords: periodontal tissues, sonodynamic therapy, histology, alveolar bone loss, animal studies